Dynamic fracture of carbon nanotube/epoxy composites under high strain-rate loading. (January 2015) - Bie, B.X.; Han, J.H.; Lu, L.; Zhou, X.M.; Qi, M.L.; Zhang, Z.; Luo, S.N.
Abstract: We investigate dynamic fracture of three types of multiwalled carbon nanotube (MWCNT)/epoxy composites and neat epoxy under high strain-rate loading ( 10 5 – 10 6 s −1 ). The composites include randomly dispersed, 1 wt%, functionalized and pristine CNT/epoxy composites, as well as laminated, ∼50 wt% CNT buckypaper/epoxy composites. The pristine and functionalized CNT composites demonstrate spall strength and fracture toughness slightly higher and lower than that of neat epoxy, respectively, and the spall strength of laminated CNT buckypaper/epoxy composites is considerably lower; both types of CNTs reduce the extent of damage. Pullout, sliding and immediate fracture modes are observed; the fracture mechanisms depend on the CNT–epoxy interface strength and fiber strength, and other microstructures such as the interface between CNT laminates. Compared to the functionalized CNT composites, weaker CNT–epoxy interface strength and higher fiber strength lead to a higher probability of sliding fracture and higher tensile strength in the pristine CNT composites at high strain rates. On the contrary, sliding fracture is more pronounced in the functionalized CNT composites under quasistatic loading, a manifestation of a loading-rate effect on fracture modes. Despite their helpful sliding fracture mode and large CNT content, the weak laminate–laminate interfaces play a detrimental role in fracture of the laminated CNT buckypaper/epoxy composites. Regardless of materials, increasing strain rates leads to pronounced rise in tensile strength and fracture toughness.